Development of the Braga Art Website as a Means for UMKM Products as an Effort to Implementation of Digital Citizenship and Local Wisdom - Laia, Lysia Nietha Marcella; Juliana, Rizal; Gulo, Hajati Ahmat Jaya (Universitas Katolik Parahyangan, 2023)
The Art Braga website is a medium used to market MSME products in Braga to make them better known to a wider audience. The importance of digital media for marketing products is supported by the development of supporting internet technology. This is proven by the increasing number of people who use the internet. The aim of this research is to provide education regarding the importance of digital media for marketing products and applying IPR in works so that MSME actors can implement digital citizenship and maintain local wisdom regarding the works of art they own. Apart from that, it collects data on painting MSMEs to be input into a website, so that it can support the amount of information obtained by consumers when accessing the website. This research uses qualitative methods and descriptive analysis which provides an overview of the environment where MSMEs operate in Braga.